UNVEILING THE FUTURE OF ARTIFICIAL INTELLIGENCE TECHNOLOGY: IS THE ACCOUNTANT GENERATION READY? - Elga Yulindisti; Ardimansyah Ardimansyah; Fiqih Yusril Mahendra; Rafles Ginting (Faculty of Economics and Business University of Mataram, 2024)
The rapid development of Artificial Intelligence (AI) has significantly impacted the accounting sector, creating both opportunities and challenges for professionals and students. This study analyzes the readiness of accounting students and practitioners in Indonesia to adopt AI technologies, focusing on their Artificial Intelligence Technology Readiness (AITR). Using the Theory of Planned Behavior (TPB) framework, the study examines the influence of practitioner status, age, gender, technology skill level (TSL), and location on AITR. Data from 100 respondents (students and practitioners) were collected through surveys and analyzed using multiple linear regression with bootstrapping. The research found that students have higher AITR than practitioners, with TSL emerging as the most significant factor. Age, gender, and location show no significant effects. These findings highlight the need for curriculum reforms integrating AI-related skills and practical experiences to meet industry demands. This study provides valuable insights for educators and policymakers to enhance the competencies of future accountants in AI-driven workplaces.